122 Toxicological effects of repetitive exposure to mig-welding fume particles on rat precision-cut lung slices. (24th April 2018) - Krabbe, J; Kanzler, S; Esser, A; Kraus, T; Brand, P; Martin, C
Abstract : Introduction: The proinflammatory effects of metal inert gas brazing (MIG) welding fumes containing zinc and copper have been demonstrated in humans. However, little is known about the specific effects on the lung. Here we examined the effects of different concentrations of welding fumes for repetitive exposure in rat precision-cut lung slices (PCLS). Methods: PCLS were prepared from agarose-filled lungs of male rats. To mimic a five day 'work week', PCLS were incubated in welding fume containing media with 1 and 0.1 µg/ml in a repetitive exposure model for 6 hours on 5 consecutive days. For the remaining 18 hours PCLS received incubation in standard incubation medium. For each day cytotoxicity was determined via WST-1 and LDH assay. To determine the maximal LDH release possible, PCLS were treated with Triton X-100 as a positive control. Result: Over all days of consecutive treatment no significant reductions of mitochondrial activity determined via WST-1 could be found in comparison to untreated controls. LDH levels in supernatants increased up to 15% of levels of positive controls treated with Triton X-100, indicating no relevant toxicity. Discussion: This is the first time repetitive toxicological effects of welding fumes on the lung have been examined in isolated lung tissue with intact microanatomy. We demonstrate that a repeated exposure for up to five days has no relevant toxic effects on lung tissue in doses comparable to a realistic occupational exposure. Lung tissue slices could be a promising model to study toxicity of welding particles and need to be investigated further.